LOCAL WISDOM OF A TYPICAL DRINK FROM MINANGKABAU; KAWA DAUN - Suci Rafifah (Pendidikan IPA, FMIPA, UNP, 2022)
Kawa Daun drink is a beverage made from dried coffee leaves and is a typical drink of West Sumatra. A survey of the process of making kawa leaf drink has been carried out by visiting the places where the manufacture of kawa leaves is spread in three regencies in West Sumatra, namely Tanah Datar District, Agam District, and Lima Puluh Kota District. This study aims to obtain information on the process of making existing and developed Kaawa Daun drinks in West Sumatra. Data were obtained by interviewing techniques, direct observation, and assisted with a list of questions. From the results of observations on the process of making existing Kaawa leaves and developing in West Sumatra it is known that there are three processes of making kahwa drinks or extraction processes namely 1) cooking (water and coffee leaves are cooked simultaneously until boiling) 2) brewing (brewed coffee leaves with hot water 80-90oC), and 3) dissolution (water is boiled until then the coffee leaves are inserted and allowed to boil for 3-5 minutes).